2012
DOI: 10.1002/ejlt.201200104
|View full text |Cite
|
Sign up to set email alerts
|

Regional and cultivar comparison of Italian single cultivar olive oils according to flavor profiling

Abstract: Geographical origin, cultivar, and olive ripening stage are important factors which affect the typical flavor profile of extra virgin olive oils. Aromatic compounds and sensorial profiles of “Casaliva”, “Frantoio”, and “Leccino” olive oils from three different Italian production regions Abruzzo (eastern‐central Italy), Lombardy (northern Italy), and Tuscany (western‐central Italy) were assessed in two cropping years and at three olive ripening stages (green, veraison, and ripe). The chemical aromatic compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 23 publications
3
30
1
Order By: Relevance
“…This misclassification may be due to similar volatile profiles of olive oils from Cobrançosa fruits collected in October and in November. Tura, Failla, Bassi, Attilio, and Serraiocco (2013) confirmed that the ripening stage influence both trans-2-hexenal and 1-penten-3-one, as well as Garcia, Magalhães, Fregapane, Salvador, and Paiva-Martins (2012) for the last compound. Prenzler et al (2007) without pre-selection of volatile compounds, found that trans-2-hexenal, hexanol, 1-penten-3-ol and cis-2-penten-1-ol, contribute towards the discrimination of maturity stages.…”
Section: Comparison Of Aroma Compounds In Galega and Cobrançosa Olivesupporting
confidence: 62%
“…This misclassification may be due to similar volatile profiles of olive oils from Cobrançosa fruits collected in October and in November. Tura, Failla, Bassi, Attilio, and Serraiocco (2013) confirmed that the ripening stage influence both trans-2-hexenal and 1-penten-3-one, as well as Garcia, Magalhães, Fregapane, Salvador, and Paiva-Martins (2012) for the last compound. Prenzler et al (2007) without pre-selection of volatile compounds, found that trans-2-hexenal, hexanol, 1-penten-3-ol and cis-2-penten-1-ol, contribute towards the discrimination of maturity stages.…”
Section: Comparison Of Aroma Compounds In Galega and Cobrançosa Olivesupporting
confidence: 62%
“…It is noted that furan formation from unsaturated fatty acids is associated with the lipid oxidation. [29] In this study, PCA was applied to assess the relationships between regions and chemical groups of volatile compounds (Fig. 1), the differences between volatile compounds depending on the region (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Abo-shoka cultivar performed two times higher olive weight compared with the Improved Nabali cultivar. Cultivar also exerts influences on the triglyceride composition (Giuffrè, 2013a), wax ester content (Giuffrè, 2013b), volatile compounds (Tura et al, 2013), fatty acid composition (Caporaso, 2016) and the fatty alcohol content (Giuffrè, 2014a(Giuffrè, , 2014b. Variety selection is one important factor, which should be considered prior to olive tree planting for increased harvesting efficiency (Ravetti, 2008).…”
Section: Cultivar/genotypementioning
confidence: 99%
“…For example, Wadi-bin Hamad area showed the highest olive fruit weight compared with the Al-Mshaqar area of all cultivars (Al-Maaitah et al, 2009). The flavor of olive oils depends on its area of geographical origin because they influenced by the environmental condition (Tura et al, 2013). The growing area has impacted on the cis-3hexenal, cis-3-hexenol, hexanal, hexanol, trans-2-hexenal, trans-3-hexenol and trans-2-hexenol (Vichi et al, 2003).…”
Section: Growing Area/altitudementioning
confidence: 99%
See 1 more Smart Citation